"We Who Have the Destiny of Musical America in Our Hands": History Speaks to Us through 100 Years of MEJ. (June 2014) - McCarthy, Marie
To mark the centennial of Music Educators Journal ( MEJ ), this article explores the relationship of music education and the making of musical America across the century. Several interwoven themes are developed to show changing narratives of American music and music education, using voices from the pages of MEJ. The themes rise and recede at different times, appearing in different guises according to the political, social, and cultural ideologies and values of the time. The author reflects on music education then and now and ends with reflections based on the first century of the journal's history.